Effectiveness of the ELSA Speak Application as a Medium for Improving Pronunciation Skill in Speaking English in Vocational High Schools - Nur' Ayunin Navia; Niko Fediyanto (Universitas Pahlawan Tuanku Tambusai, 2026)
Pronunciation is an essential component in developing students' speaking skills in learning English, especially for vocational high school students who are prepared to enter future workplaces that require effective oral communication with colleagues, clients, and industry partners. However, many vocational high school students still experience difficulties in pronouncing English words accurately. This study aims to determine the effectiveness of the ELSA Speak application in improving students' pronunciation skills. This research used a quantitative approach with a quasi-experimental design. The participants of this study were 39 students of class XI MP1 at SMK Muhammadiyah 1 Taman. Data were collected through pre-test and post-test in the form of oral pronunciation tests. The data were analyzed using SPSS through normality test, correlation test, and paired sample t-test. The results showed that the mean score increased from 73.08 in the pre-test to 81.56 in the post-test. The paired sample t-test showed a significance value of 0.000 (p 0.05), indicating a significant improvement. This suggests that AI-based applications such as ELSA Speak can serve as a viable supplementary tool in the EFL classroom, particularly for enhancing students’ pronunciation through autonomous and technology-assisted practice.